Prototipo módulo hospitalario de emergencia para la atención de desastres (2021)
Infrastructure for health is the most important and necessary at a global level, but at the same time, it is the most complex for structuring its design, this means that it is difficult to design a building in relation to health, since it has the complexity of the technologies that it integrates. With so many emergencies that have arisen over the years, cities in particular have not yet planned strategies to help with these moments of vulnerability; Therefore, this degree work focuses on analyzing the various weakness scenarios, whether they are presented by means of a natural, social or technological nature.